Drug shortage management in Alabama hospital pharmacies - Oliver W. Holmes, III; Peter J. Hughes (INNOVATIONS in Pharmacy, 2013)
Purpose: The purpose of this study is to identify effective strategies used by Alabama hospitals to manage drug shortages. Moreover, this study aims to determine if there are any relationships among hospital size, utilization of a standard policy for drug shortage management and perceived usefulness of standard procedures for drug shortages.